Clinical significance of the apoptotic index in non-small cell lung cancer - Dworakowska, Dorota (Contemporary Oncology/Współczesna Onkologia, 2005)
Apoptosis remains a physiological form of cell death, which enables elimination of damaged cells. Apoptosis is also called programmed cell death, because this process is exactly regulated by several genes including P53, BCL2 and BAX. p53 protein and bax activate apoptosis, whereas bcl-2 protein inhibits the process of programmed cell death. p53 protein activates apoptosis in response to cell injury and its proapoptotic function might be inhibited by mdm2 protein, which forms with p53 the autoregulatory feed-back loop. Additionally, a close correlation between mdm2-pRb explains how the two most important tumor suppressor genes P53 and RB cooperate in p53 depending activation of apoptosis. It seems that RB has an antiapoptotic activity, because in cells in which the function of RB was lost, apoptosis was activated due to healthy P53 gene. Disturbances in the function of tumor suppressors genes and activation of protooncogenes could result in cancer development. Proper regulation of apoptosis enables keeping a balance between cell death and proliferation. Instead of apoptosis, the cell can die due to necrosis. Apoptosis of the tumor cells was usually assessed with the use of the TUNEL technique. In current literature, the prognostic value of occurrence of apoptotic cells in lung cancer remains controversial. In this paper the author presented the clinical significance of the apoptotic index in non-small cell lung cancer